Cenozoic Tectono‐Geomorphologic Evolution of the Pamir‐Tian Shan Convergence Zone: Evidence From Detrital Zircon U‐Pb Provenance Analyses. Issue 10 (18th October 2021) - Jia, Yingying; Glotzbach, Christoph; Lü, Lixing; Ehlers, Todd A.
Abstract: The Pamir is the northwestward continuation of the Tibet‐Himalaya orogen and translated ∼50–300 km northward toward the Tian Shan in Mesozoic‐Cenozoic times. Although this region has been studied extensively over the past few decades, our knowledge of the timing of mountain building in the Pamir is incomplete. In this study, we applied provenance analyses of Cretaceous‐Pliocene sediments from the Tierekesazi section in the Pamir‐Tian Shan corridor to reconstruct the Cenozoic evolution of the Pamir‐Tian Shan orogens. Provenance data from new detrital zircon U‐Pb ages and paleocurrent measurements indicate that the main source area of sediments in the studied section shifted from the Tian Shan to the Northern Pamir at ∼41–40 Ma. When combined with published provenance data, eastward decreasing sediment transport distances suggest that the Pamir was characterized by an asymmetric drainage system with larger drainage basins developed in the western Pamir than the eastern Pamir since the late Eocene. This resulted from either eastward decrease in precipitation rate caused by the uplift of the Pamir orocline or relatively low topography of the western Pamir. Furthermore, observed east and south directed paleocurrents and a dominance of Paleozoic detrital zircon U‐Pb ages in the upper Miocene‐Pliocene sediments suggest the SW Tian Shan was uplifted and became the primary provenance of the Tierekesazi section in the late Miocene. Simultaneously, the thrust belt of the Pamir propagated into its northern foreland and the present‐day east flowing drainage system in the eastern Pamir‐Tian Shan convergence zone was established in the late Miocene. Key Points: Asymmetric drainage patterns with larger rivers in the west and small rivers in the east have been established since the late Eocene The Karakul‐Mazar terrane was uplifted and the primary source area of the Pamir‐Tian Shan corridor in the late Eocene‐middle Miocene The present east flowing drainage systems we established in the late Miocene due to the crustal shortening in the Pamir‐Tian Shan corridor